A Two-Dimensional Model for Supplier Development’ Criteria Using Meta-Synthesis Method - Laya Olfat; Maghsood Amiri; Iman Raeesi Vanani; Mansour Esmaeilzadeh (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2020)
Today, it is difficult for organizations to survive without improving supplier performance and supplier relationships or gain competitive advantage. Therefore, suppliers must be managed and developed to meet the needs of the producer company. On the other hand, the supplier's development requires the introduction of precise and comprehensive criteria. The aim of this paper is to identify the dimensions and categories of supplier development based on the criteria related to it, using the Meta-synthesis method. For this purpose, first we selected 102 studies from 136 studies, coding their texts with Atlas TI software, 23 concepts were identified for the criteria. Subsequently, through the analysis of literature, the identified concepts were classified into four tangible, intangible, environmental, and external dimensions and internal dimensions. To verify validity, triangulation of data, sources and researcher has been used. The content validity ratio and content validity index were calculated by a survey of automobile industry experts, four of the criteria were directly eliminated, and modifications and modifications were made on the criteria, and finally, 17 criteria for the development of suppliers in the automotive industry were finalized. The amount of Kappa coefficient obtained shows the reliability of the identified criteria. Finally, a two-dimensional model is proposed for the supplier-development criteria. Due to the lack of categorization of the criteria related to the supplier's development in previous studies, and in particular in domestic research, the identified criteria and their categorization can be useful for researchers in this field.